PENGARUH PENAMBAHAN EKSTRAK KULIT BUAH NAGA SEBAGAI PEWARNA ALAMI PADA KUALITAS NATA DE SOYA HASIL FERMENTASI LIMBAH CAIR TAHU DI LINGKUNGAN KEKALIK TIMUR KOTA MATARAM: THE EFFECT OF ADDING DRAGONS FRUIT EXTRACT AS NATURAL DYE ON THE QUALITY OF NATA DE SOYA FROM FERMENTATION OF TOFU LIQUID WASTE IN THE EAST KEKALIK ENVIRONMENT OF MATARAM CITY - Baiq Dewi Ratnasari; Yahdi Yahdi; Sulistiyana Sulistiyana (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2021)
Nata de soya is a food product derived from tofu liquid waste from the fermentation of Acetobacter xylinum. The addition of natural dyes in nata can improve the physical quality of nata. This study aims to determine the effect and optimum quality of the addition of dragon fruit peel extract on the quality of nata de soya. The experimental design method used in this study was a completely randomized design (CRD). The control variables in this study were 1000 mL tofu liquid waste, 4 grams of ZA Food Grade, 100 grams of sugar, and 14 days of fermentation. The independent variable was the concentration of dragon fruit peel extract, namely 0% (control), 5%, 10%, 15% and 20%. The dependent variables are water content, crude fiber content, and organoleptic (color, shape, and texture). The results showed that the variation of 20% dragon fruit peel extract affected the physical quality of nata. There was a significant effect on the quality of the water content and organoleptic (color and texture) of the nata, while the quality of the fiber content and organoleptic (shape) was not significantly affected on the quality of the dragon fruit peel extract combination nata. The optimum quality of this study was dragon fruit peel extract 20% with a water content value 88.60%, a fiber content value of 2.73%, and an organoleptic test (color, shape, and texture) with an average value of 4.85, 4.90, and 4.90. Nata de soya adalah produk pangan berasal dari limbah cair tahu hasil fermentasi Acetobacter xylinum. Penambahan pewarna alami pada nata dapat meningkatkan mutu fisik nata. Penelitian ini bertujuan untuk mengetahui pengaruh dan kualitas optimum penambahan ekstrak kulit buah naga terhadap kualitas nata de soya. Metode rancangan percobaan yang digunakan dalam penelitian ini adalah rancangan acak lengkap (RAL). Variabel kontrol pada penelitian ini adalah limbah cair tahu 1000 mL, ZA Food Grade 4 gram, gula 100 gram, dan lama fermentasi 14 hari. Variabel bebas adalah konsentrasi ekstrak kulit buah naga yaitu 0 % (kontrol), 5 %, 10 %, 15 % dan 20 %. Variabel terikatnya adalah kadar air, kadar serat kasar, dan organoleptik (warna, bentuk, dan tekstur). Hasil penelitian menunjukkan variasi ekstrak kulit buah naga 20% mempengaruhi kualitas mutu fisik nata. Ada pengaruh nyata terhadap kualitas kadar air dan organoleptik (warna dan tekstur) nata sedangkan pada kualitas kadar serat dan organoleptik (bentuk) tidak terpengaruh signifikan terhadap kualitas nata kombinasi ekstrak kulit buah naga. Kualitas optimum penelitian ini ialah ekstrak kulit buah naga 20% dengan nilai kadar air 88,60%, nilai kadar serat 2,73%, dan uji organoleptik (warna, bentuk, dan tekstur) dengan nilai rata-rata sebesar 4,85, 4,90, dan 4,90.